2020
DOI: 10.1016/j.celrep.2020.108175
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Cell RNA Expression Map of Human Coronavirus Entry Factors

Abstract: To predict the tropism of human coronaviruses, we profile 28 SARS-CoV-2 and coronavirus-associated receptors and factors (SCARFs) using single-cell transcriptomics across various healthy human tissues. SCARFs include cellular factors both facilitating and restricting viral entry. Intestinal goblet cells, enterocytes, and kidney proximal tubule cells appear highly permissive to SARS-CoV-2, consistent with clinical data. Our analysis also predicts non-canonical entry paths for lung and brain infections. Spermato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
242
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(260 citation statements)
references
References 126 publications
(177 reference statements)
16
242
1
1
Order By: Relevance
“…Furthermore, it should be taken into consideration that ACE2 expression may vary greatly among individuals due to genetic or environmental factors (59). Such intrinsic ACE2 variability has been previously observed also in other cellular contexts, with some authors reporting high ACE2 levels and others low or absent (60). In our study, localization of ACE2 in pancreatic islet endocrine cells was observed using two out of three different antibodies tested.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, it should be taken into consideration that ACE2 expression may vary greatly among individuals due to genetic or environmental factors (59). Such intrinsic ACE2 variability has been previously observed also in other cellular contexts, with some authors reporting high ACE2 levels and others low or absent (60). In our study, localization of ACE2 in pancreatic islet endocrine cells was observed using two out of three different antibodies tested.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, it should be taken into consideration that ACE2 expression may vary greatly among individuals due to genetic or environmental factors (58). Such intrinsic ACE2 variability has been previously observed also in other cellular contexts, with some authors reporting high ACE2 levels and others low or absent (59).…”
Section: Discussionsupporting
confidence: 61%
“…These exosomelike structures seem to incorporate TMPRSS2 into sperm (50). A close examination of the human sperm proteomic database also reveals the presence of related proteases TMPRSS11B and TMPRSS12 as well as FURIN (45,46), in these cells, all of which are thought to serve as activating proteases for viral infection including coronaviruses (51)(52)(53). The presence of these activating proteases and ACE2 in the sperm plasma membrane provides the possibility for the sexual transmission of the virus.…”
Section: Potential Transmission Mode Of Sars-cov-2mentioning
confidence: 95%